2005
DOI: 10.1038/labinvest.3700245
|View full text |Cite
|
Sign up to set email alerts
|

Blunted DNA synthesis and delayed S-phase entry following inhibition of Cdk2 activity in the regenerating rat liver

Abstract: Activation of the cyclin E/Cdk2 complex may play an important role in mid-G1/S-phase progression in proliferating mammalian cells. We evaluated the effect of targeted inhibition of Cdk2 activity by CYC202 (Rroscovitine) on hepatocytes proliferation in vivo after 70% partial hepatectomy (PH) in rats. In controls, Cdk2 activity and DNA synthesis peaked 24 h after PH. CYC202 abrogated Cdk2 activity, prevented BrdU incorporation and PCNA expression and increased mortality 24 h after PH. Cyclin E and Cdk2 protein e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…5B), inhibition of DNA synthesis by WY14,643 probably results from the absence of PCNA. Evidence of a relationship between cdk2 and PCNA (Sever-Chroneos et al, 2001;Starkel et al, 2005) supports this argument. Furthermore, the inability to phosphorylate cdk2 in the presence of WY14,643 suggests that this compound may operate through a cdk-activating kinase, a mechanism previously identified for mevastatin (Ukomadu and Dutta, 2003).…”
supporting
confidence: 66%
“…5B), inhibition of DNA synthesis by WY14,643 probably results from the absence of PCNA. Evidence of a relationship between cdk2 and PCNA (Sever-Chroneos et al, 2001;Starkel et al, 2005) supports this argument. Furthermore, the inability to phosphorylate cdk2 in the presence of WY14,643 suggests that this compound may operate through a cdk-activating kinase, a mechanism previously identified for mevastatin (Ukomadu and Dutta, 2003).…”
supporting
confidence: 66%
“…In addition, interference with Ras gene expression also reduced liver regeneration, presumably through reduction of cyclin E/Cdk2 expression [13]. Our results of strongly reduced liver cell proliferation using the Cdk2 inhibitor roscovitine [35] and the Ras inhibitor FTS in the present study adds further evidence for a critical role of the Ras-cyclin E/Cdk2 axis in hepatocyte proliferation. It has been suggested that Ras signalling via the MAPK pathway may be important in this process.…”
Section: Discussionsupporting
confidence: 57%
“…As shown previously by our group [35], Ckd2 kinase activity is essential for transition from G 1 -to S-phase and inhibition or reduction in its activity blocked hepatocytes in late G 1 -phase. It has been shown that Ras expression increases at a critical time point in the regenerating rat liver [10,36].…”
Section: Discussionmentioning
confidence: 50%
“…Although we did not perform a full time course of liver regeneration in the cdk2 -/- mice, a previous study has demonstrated that seliciclib impairs hepatocyte proliferation after PH. 29 Of note, another recent study found no difference in DNA synthesis at later time points after PH (48–72 hr) between cdk2 -/- and WT mice. 35 The combined data suggests that the absence of cdk2 delays but does not prevent the onset of DNA synthesis in this model, compatible with the observation that liver regeneration is driven by alternative mechanisms when one or more pathway is interrupted.…”
Section: Discussionmentioning
confidence: 92%
“…1,2 A prior study has shown that treatment with seliciclib diminishes hepatocyte proliferation after PH, 29 suggesting that cdk2 plays a role in liver regeneration. However, this drug has several targets aside from cdk2.…”
Section: Resultsmentioning
confidence: 99%